Quality of rocoto pepper (Capsicum pubescens Ruiz and Pav.) seeds in relation to extraction timing (2018)
Rocoto pepper (C. pubescens), is one of the domesticated species of the genus Capsicum in South America. Currently, its supply and demand are arising in national and global market. The aim of this study was to determine the optimal extraction timing of the seeds of C. pubescens according to physiological and physical seed qualities. Seed qualities measurement include seed weight, number of seeds per fruit, total emergence, emergence rate, mean emergence time, mean daily emergence, survival percentage, peak value and emergence value. Treatments were evaluated for comparison as follows: seed extraction ranged from 0 to 3 days after harvest (T1), and seed extraction ranged from 14 to 17 days after harvest (T2). T1 presented seeds with the best physiological qualities and a total emergence value of 84.2%, in contrast to 74.8% obtained in T2. A positive correlation was found between seed size, number of seeds per fruit and overall quality, respectively. Based on the results of this study, is recommended to use and conserve the seeds extracted immediately after harvest, as well as larger seeds from biggest fruits.